Regenerating the underutilised: a catalytic intervention for reactivation within a revived urban green artery - Musiker, Rick (My University, 2016)
Abstract This thesis focuses on identifying and satisfying opportunities through the regeneration of underutilised land in our cities. It investigates the potential and benefits of transforming these land parcels to maximise accessibility, use, and function. Consequently influencing urban renewal and urban connection. The thesis initiated through identifying the possibilities and opportunities which exist upon the Killarney Country Club site in Lower Houghton, Johannesburg. Its location, size and exposure are key to its potential, furthermore its current status makes transformation plausible and desirable. The Killarney Country Club is a sizeable strip of greenery centrally located in the Johannesburg context. It offers significant linkage opportunities throughout Johannesburg and high public exposure. In its current state it is heavily underutilised, allowing access to a select elite minority and in turn creating a stifling element in the city. Theoretically the Killarney Country Club can be described as a Heterotopic space. A space without a place, juxtaposing its context and existing as a world within a world. However, it ultimately possesses the ability to transform to meet the needs of an evolving society. These heterotopic concepts, debated by Michel Foucault, are regenerating the underutilised A Catalytic Intervention for Reactivation Within a Revived Urban Green Artery a b s t r a c t influential theories which I explore during this thesis. The success of this regenerative intervention requires a comprehensive urban framework which lays the foundations for an equally significant architectural intervention at the core of the proposal. The urban intervention includes elements of linkage, activity, high density, mixed-use and place making. The improvements see the transformation of the Killarney Country Club into an accessible, connected and active city node, which embodies a social and recreation facility. The facility promotes outdoor activity, wellness and interaction amidst a heavily altered and environmentally conscious new urban context. To attract and generate activity to the site I have proposed a public square at the heart of the transformation, on-to which is placed a catalytic architectural intervention for regeneration. The proposed built intervention is a Social + Recreation Complex which is comprised of three interconnected but separate buildings. The Social+ Recreation Centre, the Conference + Events Centre and The Exhibition Centre. The building becomes a threshold between urbanity and nature. It promotes, and most significantly, initiates and sustains the regenerative transformation.
Keywords: Urban renewal--South Africa; City planning--South Africa